Resource conservation techniques for climate change mitigation and adaptation - Saha, Soumya; Tuti, Mangal Deep; singh, Aarti; Kumar, R M; Sreedevi, B (Indian Farming, 2018)
Global temperature has increased by 0.6 ± 0.2°C with an increase of 0.17°C per decade since 1950 mostly due to enhancement of greenhouse gases. Agriculture contributes 47% and 58% of total anthropogenic emissions of N2O and CH4, respectively, which have between 25-and 298-fold global warming potential of that of CO2. The agriculture sector has potential to reduce its own emissions, and concurrently, can also reduce emissions from other sectors through removing CO2 from the atmosphere through photosynthesis. Resource Conservation Techniques viz. zero-tillage, laser land levelling, fertilizer scheduling, use of slow release of N fertilizer have potential to increase carbon (C) accumulation in soil, reduce GHG emissions, and improve water and other input-use efficiency.